The last poem of Pietro Giannone—finally decrypted. Issue 5 (2nd September 2016) - Bonavoglia, Paolo; Pellegrino, Consolato
ABSTRACT: Pietro Giannone (1791–1872) was an Italian poet and patriot, a friend and associate of Giuseppe Mazzini. In his last years, he wrote a secret poem using unusual symbols. For nearly 150 years, the poem resisted decryption attempts, but the code has recently been broken and recovered: a mix of monoalphabetic, digraphic, trigraphic signs, polyphones, and a little repertory. Some serious (but useful) flaws made decryption possible.